Changes in temperature management and outcome after out-of-hospital cardiac arrest in United Kingdom intensive care units following publication of the targeted temperature management trial. (May 2021) - Nolan, J.P.; Orzechowska, I.; Harrison, D.A.; Soar, J.; Perkins, G.D.; Shankar-Hari, M.
Abstract: Aim: To investigate how the publication of the targeted temperature management (TTM) trial in December 2013 affected the trends in temperature management and outcome following admission to UK intensive care units (ICUs) after out-of-hospital cardiac arrest (OHCA). Methods: We used a national ICU database of 1, 181, 405 consecutive admissions to 235 adult ICUs. OHCA admissions mechanically ventilated in the first 24 h in the ICU were divided into a pre-TTM trial cohort of patients admitted before publication of the TTM trial (January 2010–December 2013) and post-TTM cohort of patients admitted after TTM trial publication (January 2014–December 2017). The primary outcome variables were lowest temperature in the first 24 h in ICU and survival to hospital discharge. Results: The lowest temperature recorded in the first-24 h of admission was significantly higher in the post-TTM cohort (n = 18, 106) than in the pre-TTM cohort (n = 12, 162) (mean 34.7 (±1.6) versus 33.6 °C (±1.8); absolute difference 1.12 °C (95% CI 1.08–1.16). The post-TTM cohort had a greater prevalence of fever (>38.0 °C) (24.8% vs 14.7%; (odds ratio (OR) 1.91 (95% CI 1.80–2.03); p < 0.001)) and higher unadjusted in-hospital mortality (63.7% vs 61.6%). In a multilevel model, accounting for time trend and including site as a random effect, neither the step change in acute hospital mortality following publication of the TTM trial result (OR 1.04, 95% CI 0.95–1.15; p = 0.37), nor the change in slope (from OR 1.00 per year, 95% CI 0.97–1.04, to 1.04 per year, 95% CI 1.02–1.07; p = 0.059), was statistically significant. Adjusted analyses were limited by the models' dependence on temperature and temperature-related variables. Conclusions: The lowest temperature recorded in the first-24 h of admission in OHCA patients was higher in the post-TTM cohort compared with the pre-TTM cohort. There has been an increase in the proportion of patients with fever (>38 °C) in the first 24 h. Although crude mortality was slightly higher in the post-TTM cohort, an analysis accounting for time trend and variation between critical care units, found no significant change associated with the TTM publication.